Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

» Solve the equation 9(k − 2) = −6.
-
k = 1


Sagot :

Answer:

False

Step-by-step explanation:

9(k-2)=-6 and k=1

9(1-2)=-6

9(-1)=-6

-9=-6

No, -9 doesn't equal -6.

So this system of equations is false.

Hope this helped! :)

We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.